2011
DOI: 10.1007/s12028-011-9583-y
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Detection of Vasospasm II: EEG and Invasive Monitoring

Abstract: Several non-invasive and invasive modalities have been used to monitor patients for cerebral ischemia after subarachnoid hemorrhage. A literature search was performed to identify original research studies testing monitors that may be used in addition to the standard measures of brain function and cerebral blood flow. Fifty observational studies were identified that evaluated the role of electroencephalography, brain tissue oxygenation monitoring, cerebral microdialysis, thermal diffusion flowmetry, or near-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…94 Overall, studies of continu ous EEG are limited, and were judged to be of moderate to low methodological quality and likely to be biased. 95 Invasive brain-tissue monitoring Brain tissue oxygen monitoring measures tissue oxygen in a small region around the inserted probe, and carries risks associated with any invasive monitor that is inserted into the brain. This approach has been reported to predict onset of DCI after SAH and to correlate with outcome, although the data are limited and were judged of moderate to low quality.…”
Section: Eeg and Other Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…94 Overall, studies of continu ous EEG are limited, and were judged to be of moderate to low methodological quality and likely to be biased. 95 Invasive brain-tissue monitoring Brain tissue oxygen monitoring measures tissue oxygen in a small region around the inserted probe, and carries risks associated with any invasive monitor that is inserted into the brain. This approach has been reported to predict onset of DCI after SAH and to correlate with outcome, although the data are limited and were judged of moderate to low quality.…”
Section: Eeg and Other Technologiesmentioning
confidence: 99%
“…This approach has been reported to predict onset of DCI after SAH and to correlate with outcome, although the data are limited and were judged of moderate to low quality. 95 Brain microdialysis is another focal, invasive moni toring method that might have utility for identification and monitoring of DCI. Cerebral ischaemia is associ ated with elevated glutamate and glycerol levels and an increased lactate:pyruvate ratio.…”
Section: Eeg and Other Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The cEEG can serve as a method to detect events, which may give rise to secondary brain injury such as cerebral vasospasm, ischemia and subclinical epileptic seizures [5][6][7][8][9][10]. Clinical seizures have been reported to occur in 8-43 %, and subclinical EEG seizures have been reported in 3-36 % of patients treated at neuro-intensive care units [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been developed to detect and monitor signs of vasospasm including monitoring ischemic metabolites (72, 73). Microdialysis catheters were placed in the vascular territory most likely to be affected by vasospasm and it was shown that cerebral glucose was significantly lower in SAH patients presenting signs of clinical vasospasm than in asymptomatic patients (74).…”
Section: Subarachnoid Hemorrhage and Glucosementioning
confidence: 99%